The Burden of Malaria in the Democratic Republic of the Congo. (14th October 2020) - Deutsch-Feldman, Molly; Parr, Jonathan B; Keeler, Corinna; Brazeau, Nicholas F; Goel, Varun; Emch, Michael; Edwards, Jessie K; Kashamuka, Melchior; Tshefu, Antoinette K; Meshnick, Steven R
Abstract: Despite evidence that older children and adolescents bear the highest burden of malaria, large malaria surveys focus on younger children. We used polymerase chain reaction data from the 2013–2014 Demographic and Health Survey in the Democratic Republic of Congo (including children aged <5 years and adults aged ≥15 years) and a longitudinal study in Kinshasa Province (participants aged 6 months to 98 years) to estimate malaria prevalence across age strata. We fit linear models and estimated prevalences for each age category; adolescents aged 10–14 years had the highest prevalence. We estimate approximately 26 million polymerase chain reaction–detectable infections nationally. Adolescents and older children should be included in surveillance studies. Abstract : We estimated that older children and adolescents aged 5–14 years, a group often excluded from national malaria studies, have the highest prevalence of malaria infections in the Democratic Republic of the Congo.